2017
DOI: 10.1016/j.media.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

When machine vision meets histology: A comparative evaluation of model architecture for classification of histology sections

Abstract: Classification of histology sections in large cohorts, in terms of distinct regions of microanatomy (e.g., stromal) and histopathology (e.g., tumor, necrosis), enables the quantification of tumor composition, and the construction of predictive models of genomics and clinical outcome. To tackle the large technical variations and biological heterogeneities, which are intrinsic in large cohorts, emerging systems utilize either prior knowledge from pathologists or unsupervised feature learning for invariant repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Alternatively, a database of images consisting of malignant and nonmalignant specimens could be presented to allow the computer program to determine how to best differentiate between the two categories and then judge the success of the program by presenting it with new slides to verify its accuracy. If successful, the process by which the computer reaches its conclusions is of less importance if it is better at predicting the final result than our current knowledge and rule‐based system .…”
Section: Machine Learning (Ml) At a Glancementioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, a database of images consisting of malignant and nonmalignant specimens could be presented to allow the computer program to determine how to best differentiate between the two categories and then judge the success of the program by presenting it with new slides to verify its accuracy. If successful, the process by which the computer reaches its conclusions is of less importance if it is better at predicting the final result than our current knowledge and rule‐based system .…”
Section: Machine Learning (Ml) At a Glancementioning
confidence: 99%
“…This approach has been used in histological specimens and has even been crudely used in ‘reverse image searching’ by using images of specimens and utilizing the search engine to find similar images . Similarly, this process of deriving output variables from previous examples of known input variables allows for regression analysis, a concept commonly used in statistics with the difference being potential iterative improvement in accuracy of prediction by learning to progressively augment the prediction algorithm along with ability to deal with more variables and model complex nonlinear relationships between independent and dependent variables .…”
Section: Supervised Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt SPM to construct tissue morphometric context [25], [28]–[31] as the final representation for tissue classification. Let V = [ v 1 , …, v T ] ∊ ℝ SKW×T be the feature set of T feature vectors with dimension SKW .…”
Section: Evaluation Of Mscsc On Regular Classification Tasksmentioning
confidence: 99%
“…In comparing multiple machine-learning strategies, it was found that the combination of supervised cellular morphology features and predictive sparse decomposition DL features provided the best separation of benign and malignant histology sections. [ 47 ] Wang et al . were able to detect mitosis in breast cancer histopathology images using the combined manually tuned cellular morphology data and convolutional neural net features.…”
Section: Ethodsmentioning
confidence: 99%